Effect of EGR dilution on combustion, performance and emission characteristics of a diesel engine fueled with n-pentanol and 2-ethylhexyl nitrate additive. (15th November 2018) - Pan, Mingzhang; Huang, Rong; Liao, Jinyang; Ouyang, Tiancheng; Zheng, Zeyuan; Lv, Delin; Huang, Haozhong
Highlights: Blends of n -pentanol/diesel could reduce soot emission and particulate concentration. Exhaust gas recirculation significantly reduces NOX emissions with n -pentanol/diesel blends. The effect of cetane number on ignition delay is more prominent for P50 at higher EGR rates. The addition of EHN to P50 can improve combustion stability and increase thermal efficiency. Combined EHN with n -pentanol decreased soot-NOX emissions but mildly changed BTE. Abstract: The n -pentanol/diesel dual-fuel coupled with EGR (exhaust gas recirculation) technology could simultaneously reduce soot and nitrogen oxide (NOX ) emissions discharged from the compression ignition engine. However, under high EGR rates, the low cetane number of the n -pentanol/diesel dual fuel resulted to combustion deceleration behavior. Because the combustion rate has a significant influence on the thermal efficiency of the engine, it was necessary to add 2-ethylhexyl nitrate (EHN) as a cetane improver to fuel mixtures to ensure that the n -pentanol/diesel fuel has appropriate combustion characteristics. In this study, it was attempted to investigate the performance and emission of a four-cylinder, turbocharged diesel engine with EHN fueled with n -pentanol/diesel blends at varying EGR rates. The five tested fuels included pure diesel (P0), and a mixture of 50% n -pentanol and 50% diesel (P50). Moreover, EHN was added to P50 at ratios of 0.5, 1, and 2%. The results showed that P50 could reduce soot emission, nucleation and accumulation mode particles. However, the burning speed and brake thermal efficiency (BTE) were notably reduced, and emissions of hydrocarbon (HC) and carbon monoxide (CO) significantly increased. With the EGR technology, NOX emission was significantly reduced. When EHN was added to P50, engine ignition delay was shortened, BTE increased, and HC and CO emissions were substantially reduced. The use EGR technology combined with n -pentanol and EHN simultaneously reduced soot and NOX emissions, and only slightly reduced BTE.